Surgical hip dislocation vs arthroscopy for fixation of subfoveal femoral head fractures: A new technique for Pipkin type 1 fractures - Aprato, Alessandro; Buzzone, Marco; Di Benedetto, Paolo; Massè, Alessandro (Acta Biomedica Atenei Parmensis, 2021)
Background. Reduction and fixation of Pipkin type I femoral head fractures may be performed either via surgical dislocation either via hip arthroscopy but to our knowledge no studies compared those techniques. Aim of our study is to compare (1) Fracture reduction quality, (2) modified Harris hip score at a minimum of 2 years, and (3) Frequency of complications in a case series of patients with femoral head fractures treated with those approaches. Methods Five cases of arthroscopic fixation of femoral head fracture (AG) have been compared with our historical cohort (8 patients, SDG). Patient demographic, injury, and surgical variables as well as complications were recorded and retrospectively evaluated. Radiographic outcome was scored according to Matta’s criteria on postoperative radiographs and clinical outcomes were evaluated with the modified Harris hip score. Results Fracture reduction was anatomic in five hips and imperfect in two in the SDG while four hip were classified as anatomic and one imperfect in the AG. The mean clinical scores were significantly different between the two groups (p=0.03): 88 points in SDG (SD 7) and 94 points in AG (SD 5). In the SDG, one patient developed symptomatic femoral head AVN and one had heterotopic ossification. In the AG, no complication (heterotopic ossification and AVN) but one grade I sign of arthritis were noted. Conclusions Arthroscopic reduction and fixation of Pipkin type I fracture shows radiographic results comparable to surgical dislocation but better clinical results and lower rate of comorbidity.